Pemberian air rebusan kentang pada media Murashige-Skoog terhadap pertumbuhan protokorm anggrek sendu (Grammatophyllum stapeliiflorum) secara in vitro - Fitria Elysye Ningrum; Mayta Novaliza Isda (Universitas Lancang Kuning, 2022)
Grammatophyllum stapeliiflorum is one of the most popular orchid species because of its beauty and is characterized by the shape of the flower stalk that sticks down and the brown flowers with white and yellow spots that look like drops of water or sad. This type of orchid is almost extinct and is rarely found in its natural habitat, so it is necessary to perform in vitro propagation of orchids. The culture in vitro method is one of the most effective methods for propagating rare orchids. This study aimed to determine the effect of adding potato water on protocorm growth and determine the best concentration for the growth of G. stapeliiflorum protocorm in vitro. This study used a Completely Randomized Design (CRD) with the addition of potato water (concentrations 0, 50, 100, 150, and 200 ml/L) on Murashige-Skoog (MS) medium. The results showed that the percentage of live explants was 100% in all treatments. The addition of potato water to MS medium had no effect on the percentage of live explants but still affected the growth percentage of Protocorm-like bodies (PLBs) in vitro. The best concentration of potato water for the protocorm growth of G. stapeliiflorum in vitro to MS medium was at a concentration of 150 ml/L, which was indicated by the highest percentage of PLBs growth at 100% and the color of PLBs green (2.5GY 6/8) compared to other potato water treatments and controls.